Summary of Guidelines for Infection Prevention and Control for Flexible Gastrointestinal Endoscopy - Lawrence Hookey; David Armstrong; Rob Enns; Anne Matlow; Harminder Singh; Jonathan Love (Canadian Journal of Gastroenterology)
BACKGROUND: High-quality processes to ensure infection prevention and control in the delivery of safe endoscopy services are essential. In 2010, the Public Health Agency of Canada and the Canadian Association of Gastroenterology (CAG) developed a Canadian guideline for the reprocessing of flexible gastrointestinal endoscopy equipment.